PEER TUTORS AS CATALYSTS FOR BIOLOGY LEARNING - Rangkuty, Sailana Mira (Jurnal Pelita Pendidikan, 2025)
This study aims to examine the role of peer tutors as a catalyst in improving Biology learning. The background of this study is the low level of student engagement and conceptual understanding in conventional Biology learning. Peer tutoring is a collaborative learning strategy that encourages interaction and communication between students. This study used a quantitative method with a quasi-experimental design involving an experimental class and a control class. The experimental class implemented peer tutoring, while the control class used conventional learning. Data were collected through learning outcome tests, observations, and student response questionnaires. The results showed that peer tutoring significantly improved student engagement and learning outcomes. Thus, peer tutoring is effective as a catalyst in Biology learning.